Assessing the Safety Level of Hospitalized Patients: Analyzing Patient Activities - Sayedeh Somayyeh Mousavipour; Mousa Jabbari; Mahnaz Saremi; Abbas Ebadi; Ehsan Shariat Bahadori; Davoud Khorasani Zavareh (Acta Medica Iranica)
One of the important issues in health care systems that affect safety-related behaviors and reduce medical errors is to improve the safety level of the hospitalized patients. The aim of this study was to evaluate the level of safety of the hospitalized patients by analyzing the patient's activities. In the present study, all activities of the hospitalized patients were considered as one job, and the occupational safety analysis technique was used. For this purpose, all the activities of hospitalized patients from the time of entering the hospital to the time of leaving the hospital were identified and by forming a team of specialists in the field of patient care, a list of all possible risks in different stages of patient activities was determined. To assess the risk, the risk matrix model, which is one of the risk assessment models, was used. Experts' opinions were used to rank the risk, and finally the risk level of the identified hazards was determined before and after the control measures. The results showed that the risks in 6 stages for the patient include the patient entering the hospital, patient admission in the ward, patient entry into the room, hospitalization in the room, patient transfer for medical and diagnostic purposes and patient discharge from the hospital. There are a total of 79 potential hazards. The results showed that by managing the four types of risks "Struck against", "Fall to below", "Fall same level", "Struck by", which are among the most important risks that threaten the hospitalized patients, more than 50% of potential risks is reduced. The findings showed that the recurrence and severity of risk and, consequently, the level of risk identified in different stages of hospitalization are different. Therefore, improving the level of management and prioritization and providing the controlling and the suggested solutions, which are the main management tasks in a hospital, can improve the safety of the hospitalized patients.